PELATIHAN KERJA, MOTIVASI DAN PENGEMBANGAN KARIR PENGARUHNYA TERHADAP KINERJA KARYAWAN PADA PT. RIFAN FINANCINDO BERJANGKA SOLO - Siti Mufidah; Bambang Mursito; Eny Kustiyah (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study was to determine the effect of job training, motivation and career development on employee performance The population in this study was PT Rifan Financindo Berjangka Solo. The sample in this study were 50 respondents. The results of testing hypothesis 1 which states the effect of job training on employee performance shows that job training has an effect on employee performance. Hypothesis 2 test results explain that motivation influences employee performance. The results of hypothesis 3 conclude that career development influences employee performance. Simultaneous testing results explain that job training, motivation and career development together affect employee performance. Keywords: job training, motivation, career development.